African music in Rhodesian native eduction - McHarg, James (International Library of African Music, 1958)
Being the transcription of a talk recently given by the author to a group of visiting educationists at the Leverhulme Conference in Southern Rhodesia. There are, in addition, certain intrinsic qualities in African folk music which make its preservation or cultivation a difficult matter in these days of easy communications. Father A.M. Jones, of Northern Rhodesia, who has given long years to the study of African music, refers to these difficulties in his critical essay, “The Study of African Musical Rhythm”. He describes an attempt to record, in notation, an African song by what he calls the Direct Method.
Keywords: Musical notation; Music; Ethnomusicology; Education; Northern Rhodesia; Southern Rhodesia; Zimbabwe; Native Eduction; African Music